2022
DOI: 10.22159/ijpps.2022v14i12.46191
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study on Prevalence and Treatment of Urinary Tract Infections in a Tertiary Care Teaching Hospital in Telangana State

Abstract: Objective: To study the Prevalence of urinary tract infections and related risk factors and to study the Management of urinary tract infections. Methods: This was a prospective observational study conducted in General Medicine Department, Osmania General Hospital (OGH), a tertiary care teaching hospital in Telangana State, where patients presenting or highly suspicious of having UTIs were included in the study. Pregnant women, Children, Patients who are not willing to participate were excluded from the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
0
0
1
Order By: Relevance
“…Thuốc kháng nấm có thể hoạt động theo hai cơ chế là tiêu diệt trực tiếp tế bào nấm hoặc ngăn chặn tế bào nấm phát triển. Bằng cách nhắm vào các cấu trúc cần thiết trong tế bào nấm nhưng không cần thiết trong tế bào con người, các thuốc chống nấm giúp chống lại nhiễm trùng do nấm mà không làm ảnh hưởng đến tế bào của cơ thể [9]. Để phát hiện kịp thời và điều trị nấm da hiệu quả nhất là bệnh nhân có bệnh đi kèm hay đã sử dụng bừa bãi thuốc kháng sinh, corticosteroid, rút ngắn thời gian điều trị và giảm thiểu tác dụng không mong muốn nhằm đem lại cho bệnh nhân chất lượng cuộc sống tốt hơn và giảm bớt gánh nặng về kinh tế, chúng tôi đã tiến hành nghiên cứu đề tài: "Nghiên cứu tình hình và đánh giá kết quả điều trị nấm da…”
Section: đặT Vấn đềunclassified
“…Thuốc kháng nấm có thể hoạt động theo hai cơ chế là tiêu diệt trực tiếp tế bào nấm hoặc ngăn chặn tế bào nấm phát triển. Bằng cách nhắm vào các cấu trúc cần thiết trong tế bào nấm nhưng không cần thiết trong tế bào con người, các thuốc chống nấm giúp chống lại nhiễm trùng do nấm mà không làm ảnh hưởng đến tế bào của cơ thể [9]. Để phát hiện kịp thời và điều trị nấm da hiệu quả nhất là bệnh nhân có bệnh đi kèm hay đã sử dụng bừa bãi thuốc kháng sinh, corticosteroid, rút ngắn thời gian điều trị và giảm thiểu tác dụng không mong muốn nhằm đem lại cho bệnh nhân chất lượng cuộc sống tốt hơn và giảm bớt gánh nặng về kinh tế, chúng tôi đã tiến hành nghiên cứu đề tài: "Nghiên cứu tình hình và đánh giá kết quả điều trị nấm da…”
Section: đặT Vấn đềunclassified
“…A study done in Telangana, a state in southern India, found that UTIs have been associated with multidrugresistant uropathogens, as well as with comorbidities such as diabetes, hypertension and chronic kidney disease. 6 The aim of the study is to evaluate the prevalence of bacterial pathogens associated with UTIs, along with the minimum inhibitory concentration (MIC) determining resistance to various antibiotics, especially in reference to the outpatient department.…”
Section: Introductionmentioning
confidence: 99%